PEMANFATAAN CIPLUKAN (PHYSALIS ANGULATA) SEBAGAI TANAMAN OBAT HIPERTENSI DI DESA MOHILIKECAMATAN AMANDRAYA KABUPATEN NIAS SELATAN - Irma Susanti Laia (Universitas Nias Raya, 2022)
This study aims to determine the use of ciplukan as a hypertension drug in Mohili village, Amandraya District, South Nias Regency. The source of data in this study is primary and secondary. Data collection techniques in this study were interview and documentation. Data analysis techniques in this study were data reduction, using data presentation and drawing conclusions. The conclusion is that people with hypertension in Mohili village, Amandraya sub-district, sout Nias district use ciplukan as the mst consumed hypertension drug, namely ciplukan boiled water around 80% then about 20% consume ciplukan fruit in a fresh state. And the suggestion is that this research is expected to be a source in regards to knowing the benefitts of the ciplukanplant as a hypertension medicinal plant, especially in Mohili village.